DETERMINANTS OF IMMEDIATE AND DELAYED RECALL PERFORMANCE FOLLOWING PEDIATRIC CONCUSSION. Issue 7 (30th July 2021) - Wingerson, Mathew J.; Wilson, Julie C.; Seehusen, Corrine N.; Walker, Gregory; Howell, David R.
Background: The assessment of cognitive functioning, including attention, memory, and concentration is one component of concussion evaluation. 1-3 Immediate and delayed recall tasks are clinical assessments of cognitive functioning which evaluate memory performance post-injury. 2 These tasks require patients to verbally recall as many items as possible from a word list both immediately after the list is administered and following a 5-minute delay. 2 While previous studies have used a 5-word recall list (SCAT3), 4 few have investigated the determinants of performance using a 10-word recall list (SCAT5). Purpose: The purpose of the investigation was to identify demographic, injury, and clinical test characteristics associated with immediate and delayed recall performance using the SCAT5 10-word recall test. Methods: We conducted a retrospective chart review collecting demographic (age, sex, history of concussion, relevant medical history), injury [time of clinical presentation, loss of consciousness (LOS), neuroimaging], and clinical (symptom inventory, m-BESS, tandem gait) characteristics, as well as immediate and delayed recall performance on a 10-word list. Results: Patients seen within 14 days of concussion (n=125; 15.2±1.6 years of age; 45% female; evaluated 6.9±3.4 days post-injury) were included in the analysis. Patients 15 years or older performed significantly better on both immediate and delayed recall tasks than those younger than 15 years of age (Table 1). In addition, patients who reported a diagnosis of ADD or ADHD accurately recalled fewer items during the delayed recall task (Table 1). No injury characteristics were associated with better or worse memory performance (Table 2). Patients who performed better on immediate recall reported fewer symptoms, made fewer m-BESS errors, and performed better on cognitive tasks during dual-task tandem gait (Table 3 & 4). Conclusion: Our data indicate immediate and delayed recall performance is associated with age, symptom severity, balance, and cognitive accuracy in tandem gait. Specifically, patients younger than 15 years of age and those reporting higher symptom severities demonstrated worse performance on both immediate and delayed recall tasks. Furthermore, patients reporting ADD/ADHD did not demonstrate a performance difference on immediate recall relative to peers but performed significantly worse during delayed recall testing. Additional patient characteristics of sex, concussion history, timing of clinical presentation, and injury characteristics (LOC or need for neuroimaging) were not associated with immediate and delayed recall performance. As such, clinicians using the SCAT5 word recall test during concussion evaluation should consider these patient characteristics when interpreting memory performance. References: McCrory P, Meeuwisse W, Dvořák J, et al. Consensus statement on concussion in sport-the 5 th international conference on concussion in sport held in Berlin, October 2016. Br J Sports Med . 2017;51(11):838-847. doi:10.1136/bjsports-2017-097699 Echemendia RJ, Meeuwisse W, McCrory P, et al. The Sport Concussion Assessment Tool 5th Edition (SCAT5): Background and rationale. Br J Sports Med . 2017;51(11):848-850. doi:10.1136/bjsports-2017-097506 McCrea M. Standardized Mental Status Testing on the Sideline After Sport-Related Concussion. J Athl Train . 2001;36(3):274-279. McCrea M, Kelly JP, Randolph C, et al. Standardized assessment of concussion (SAC): on-site mental status evaluation of the athlete. J Head Trauma Rehabil . 1998;13(2):27-35. doi:10.1097/00001199-199804000-00005 Tables/Figures: